PENGARUH MOTIVASI BELAJAR, PENYALAHGUNAAN TEKNOLOGI INFORMASI DAN INTEGRITAS MAHASISWA TERHADAP PERILAKU KECURANGAN AKADEMIK MAHASISWA AKUNTANSI SEBAGAI CALON AKUNTAN (Studi Pada Mahasiswa Akuntansi Universitas Islam Malang) - Nadliyah Wardha Miftahul Jannah; Anik Malikah; Arista Fauzi Kartika Sari (e_Jurnal Ilmiah Riset Akuntansi, 2020)
The purpose of this study was to determine the effect of learning Motivation, misuse of Information Technology, and Student Integrity on Academic Cheating. The population in this study were students of the Accounting Study Program of Malang Islamic University class of 2016. The sample was selected using random sampling and obtained 258 students. Ths research using multiple linear regression models. The results of this study indicate that Student Motivation and Integrity have no influence on academic cheating. Whereas misuse of Information Technology has an influence on academic cheating.Keywords: Motivation, Misuse of Information Technology, Integrity, academic cheating.